Alcohol Consumption Accumulation of Monocyte Derived Macrophages in Female Mice Liver Is Interferon Alpha Receptor Dependent - Alharshawi, Khaled; Fey, Holger; Vogle, Alyx; Klenk, Tori; Kim, Miran; Aloman, Costica (Frontiers in Immunology, 2021)
Monocytes develop in the bone marrow from the hematopoietic stem cells and represent heterogeneous phagocyte cells in the circulation. In homeostatic and inflammatory conditions, after recruitment into tissues, monocytes differentiate into macrophages and dendritic cells. Alcohol use causes about 3.3 million worldwide deaths per year, which is about 5.9% of all deaths. In the United States and Europe, alcohol use disorders represent the fifth leading cause of death. Females are more susceptible to alcoholic liver injury in both humans and mice. Strikingly, we still do not know how much of this difference in tissue injury is due to the differential effect of alcohol and its toxic metabolites on a) parenchymal or resident cells and/or b) immune response to alcohol. Therefore, we used a model of chronic alcohol exposure in mice to investigate the dynamics of monocytes, an innate immune cell type showed to be critical in alcoholic liver injury, by using immunophenotypic characterization. Our data reveal a sex-dimorphism of alcohol response of hepatic Ly-6Clo monocytes in female mice that is interferon receptor alpha dependent. This dimorphism could shed light on potential cellular mechanism(s) to explain the susceptibility of females to alcoholic immunopathogenesis and suggests an additional targetable pathway for alcoholic liver injury in females.